Frequency of in-Hospital Mortality in Acute Myocardial Infarction Patients with Metabolic Syndrome - Shahbaz Ali Shah, Uzair Abbas, Naveed Ahmed Shaikh, Mir Fahad Hussain Talpur, Kamran Nadeem, Salik Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Metabolic syndrome is one of the major public health issues worldwide. It is a pattern of physical conditions and metabolic abnormalities, commonly occurring together and increases an individual's risk of developing type 2 diabetes mellitus and atherosclerotic cardiovascular disease. Aim: To determine the frequency of in hospital mortality and in acute myocardial infarction patients with metabolic syndrome and its association with components of metabolic syndrome. Study Design: Prospective cross-sectional study Place and Duration of Study: National Institute of Cardiovascular Diseases (NICVD), Karachi from 1st May 2019 to 31st December 2020. Methodology: Two hundred and ten patients with acute myocardial infarction were taken and assessed for metabolic syndrome Participants of either gender having age 18-70 years were included in the study. Demographic, clinical characteristics and in-hospital mortality were recorded. Results: Mean age of the participants was 55.68±7.81 years. Total 88 (~41%) were female and 122 (~58%) were male. Thirty two (15.2%) participants had in-hospital mortality. Moreover, the in-hospital mortality was associated with higher age, waist circumference, and high triglyceride levels with p values <0.05. Conclusions: The waist circumference and high triglyceride component of metabolic syndrome were found to be associated with high mortality in patients who presented with acute myocardial infarction. It is essential therefore for focus on these modifiable risk factors associated with higher mortality as a secondary prevention strategy.